HODOWLA BYDŁA W STAROŻYTNYM RZYMIE - Kuszewska, Katarzyna (Collectanea Philologica, 2013)
The Romans believed that they originated from shepherds, and that the profession of a farmer was considered a noble occupation. In both agriculture and pastoralism the crucial role played cattle. Thanks to a very well-preserved agronomic Latin literature, we can accurately describe the cultures of these animals in ancient Rome. The most important sources of knowledge are Cato the Elder, Varro, Columella and Palladius. Farming description contains the information of the optimal age, race and appearance of the animal on which you need to pay attention when buying cattle. It also describes the most appropriate living conditions on the farm, such as animal housing, nutrition, health as well as breeding (the best age to breed, length of pregnancy, care of young animals and castration). Moreover, it provides valuable knowledge about most common diseases and their treatment and the benefits of keeping the animal. The description presented in an ancient literature nowadays allows the building of a big picture on the issue of breeding and keeping cattle.